2018
DOI: 10.5539/jas.v10n9p17
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Production Systems: Evaluation of Intercropping System in Coffee Plantations in Rwanda

Abstract: Intercropping is an agricultural practice consisting in planting two or several crops in the same field simultaneously. This production system appeared to offer an excellent several advantages. While intercropping has been widely practiced since ancestral times, there was a lack of data in Rwanda on the kind of intercrops mostly used and on farmers' perception of their utility and constraints. The main objectives of this work were (1) to assess the different food crops associated with coffee trees in Rwanda an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Studies integrating beans and other food crops in coffee plots have already been carried out in the EAC region, especially in Kenya. In Rwanda, for example, Harelimana et al (2018) found that common beans (Phaseolus vulgaris L.) and soybeans (Glycine max L.) were the most coffee intercropped plants. An experiment in Kenya has concluded that coffee yields were not significantly affected by rows of beans (Mwakha et Ngugi 1990) while another experiment in Kenya on young coffee concluded that several food crops should be profitably intercropped with coffee (Njoroge & Kimemia, 1995).…”
Section: Figure 4: Food Crops Used As Intercrops With Coffeementioning
confidence: 99%
“…Studies integrating beans and other food crops in coffee plots have already been carried out in the EAC region, especially in Kenya. In Rwanda, for example, Harelimana et al (2018) found that common beans (Phaseolus vulgaris L.) and soybeans (Glycine max L.) were the most coffee intercropped plants. An experiment in Kenya has concluded that coffee yields were not significantly affected by rows of beans (Mwakha et Ngugi 1990) while another experiment in Kenya on young coffee concluded that several food crops should be profitably intercropped with coffee (Njoroge & Kimemia, 1995).…”
Section: Figure 4: Food Crops Used As Intercrops With Coffeementioning
confidence: 99%
“…Common beans are usually intercropped with maize, tobacco, or coffee in Colombia ( Santalla et al, 2001 ; Iannetta et al, 2013 ; Kumar-Singh et al, 2013 ; Harelimana et al, 2018 ). Intercropping can be practiced as a way of diversifying the number of crops grown in the farm to generate more income sources.…”
Section: Data and Descriptive Analysismentioning
confidence: 99%
“…Applying coffee farming with a polyculture model is one of the alternatives that can be used to improve land use and increase farmers' incomes [5]. The polyculture model of coffee farming business on other plantation crops simultaneously functions as productive shade plants.…”
Section: Introductionmentioning
confidence: 99%